2022
DOI: 10.3389/fpsyg.2022.823496
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Subjective Perceptions of Happiness From India

Abstract: The present study aimed at understanding the subjective perception of happiness in a sample of Indian participants from diverse socio-economic backgrounds. Using convenience sampling, individual interviews were conducted with 60 participants aged between 19 to 73 years (M Age = 40 years). This study employed reflexive thematic analysis to analyse the written transcripts. Nine themes were generated which captured the essence of happiness for Indians—Feelings and Expressions of Happiness; Human Ties and Happines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Research has indicated that improving young urban adults' social and family settings, educational opportunities and economic prospects in Malaysia could have a positive impact on their happiness perception (Zaremohzzabieh, Samah, Samah, & Shaffril, 2019). Additionally, external factors such as maintaining strong social relationships, professional and personal growth, recognition, good health and access to natural environments were found to improve individual happiness in a case study conducted in India (Singh et al, 2022). Hence, these qualities are important to consider when developing policies and interventions aimed at promoting happiness and wellbeing in young adults.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that improving young urban adults' social and family settings, educational opportunities and economic prospects in Malaysia could have a positive impact on their happiness perception (Zaremohzzabieh, Samah, Samah, & Shaffril, 2019). Additionally, external factors such as maintaining strong social relationships, professional and personal growth, recognition, good health and access to natural environments were found to improve individual happiness in a case study conducted in India (Singh et al, 2022). Hence, these qualities are important to consider when developing policies and interventions aimed at promoting happiness and wellbeing in young adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotions play a significant role in determining an individual's level of happiness and are often reliable indicators of subjective well-being. Other factors that contribute to happiness include strong relationships with family members, material resources and needs, good health, spiritual beliefs and personal achievements (Singh, Bandyopadhyay, & Saxena, 2022). Research by Lambert et al (2022) suggests that low levels of subjective well-being are often associated with unhappiness and negative behavioural patterns, while physical health indicators such as regular physical activity and quality sleep are linked to higher levels of subjective well-being and more stable overall well-being profiles.…”
Section: Household Income Class In Malaysiamentioning
confidence: 99%
“…Lay conceptualisation popularly defines wellbeing in terms of its determinants and impediments. The facilitating factors include (but are not limited to) living a meaningful life, spending time with friends and family, maintaining physical and mental health, achieving professional and academic success, financial stability, pro-sociality, pursuing hobbies, being spiritual and religious, being an extravert, listening to music and being surrounded by nature (Lu and Shih, 1997; Delle Fave et al , 2016; Trinh and Khanh, 2019; Black and Kern, 2020; Singh et al , 2020; Singh et al , 2022). Inhibitors are anything that prevents an individual from deriving happiness from the aforementioned factors.…”
mentioning
confidence: 99%